The interrelatedness between infants’ communicative gestures and lexicon size: a longitudinal study - Cadime, Irene Maria Dias (2017)
Research has shown a close relationship between gestures and language development. In this study, we investigate the cross-lagged relationships between diﬀerent types of gestures and two lexicon dimensions: number of words produced and comprehended. Information about gestures and lexical development was collected from 48 typically developing infants when these were aged 0;9, 1;0 and 1;3. The European Portuguese version of the MacArthur–Bates Communicative Development Inventory: Words and Gestures (PT CDI:WG) was used. The results indicated that the total number of actions and gestures and the number of early gestures produced at 0;9 and at 1;0 year predicted the number of words comprehended three months later. Actions and gestures’ predictive power of the number of words produced was limited to the 0;9–1;0 year interval. The opposite relationship was not found: word comprehension and production did not predict action and gestures three months later. These results highlight the importance of non-verbal commu- nicative behavior in language development.